PENGARUH UKURAN DEWAN KOMISARIS, DIVERSITAS GENDER DIREKSI DAN UKURAN KOMITE AUDIT TERHADAP KINERJA PERUSAHAAN DIMODERASI OLEH UKURAN PERUSAHAAN (Studi kasus perusahaan BUMN Periode 2019-2023) - Rahmadania, Asti; Hamdi, Mukhlizul; Karimi, Kasman (Jurnal Ekonomi Sakti, 2025)
This study aims to determine whether company size is able to strengthen the relationship between the size of the board of commissioners, gender diversity in the board of directors, and the size of the audit committee on company performance. The objects of this study include State-Owned Enterprises (BUMN) during the period 2019 to 2023, with a sample size of 14 companies. Data analysis was carried out using the Moderated Regression Analysis (MRA) technique with the help of SPSS software version 23. The results of the analysis show that: (1) the size of the board of commissioners has a positive and significant effect on company performance, (2) gender diversity in the board of directors does not show a significant effect on company performance, (3) the size of the audit committee also does not have a significant effect on company performance, (4) company size strengthens the relationship between the size of the board of commissioners and company performance, (5) company size does not strengthen the effect of gender diversity in the board of directors on company performance, and (6) company size does not strengthen the effect of the size of the audit committee on company performance.